2017
DOI: 10.1111/jai.13372
|View full text |Cite
|
Sign up to set email alerts
|

Spawning lake sturgeon (Acipenser fulvescens Rafinesque, 1817) and their habitat characteristics in Rainy River, Ontario and Minnesota

Abstract: Summary Lake Sturgeon (Acipenser fulvescens) spawning habitat in the Rainy River was studied in light of the ongoing review of the rules governing water levels upstream that affect discharge rates through the International Falls dam. The objectives of this study were to assess the current status of spawning Lake Sturgeon below the dam by: (i) evaluating weight–length relationships, condition, age and growth; (ii) identifying spawning locations and characterizing its physical attributes; and, (iii) evaluating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Furthermore, the estimated interaction time of eggs and sperm in our simulations was approximately 3.32 s under high flow and 10.16 s under low flow within a laminar environment. Lake sturgeon actively spawn under considerably higher and turbulent river flow conditions than we were able to simulate experimentally (e.g., 1.90 m 3 /s; Smith et al, 2017). Thus, the hypothesized negative effect of water velocity on egg fertilization may not be realized until higher water velocities are experienced.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Furthermore, the estimated interaction time of eggs and sperm in our simulations was approximately 3.32 s under high flow and 10.16 s under low flow within a laminar environment. Lake sturgeon actively spawn under considerably higher and turbulent river flow conditions than we were able to simulate experimentally (e.g., 1.90 m 3 /s; Smith et al, 2017). Thus, the hypothesized negative effect of water velocity on egg fertilization may not be realized until higher water velocities are experienced.…”
Section: Discussionmentioning
confidence: 74%
“…Water velocity is a key physical stream factor that has been important in spawning duration and spawning site selection (Auer 1996a, Forsythe et al, 2011; Forsythe et al, 2012; Smith, Smokorowski, & Power, 2017). However, the effects of water velocity on egg fertilization was minimal in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dams and dam operations can negatively affect lake sturgeon and their habitats (Houston, ; Auer, , ; Ferguson & Duckworth, ; Peterson, Vecsei, & Jennings, ; Randall, ; Haxton, Friday, Cano, & Hendry, ; Haxton, Friday, Cano, & Hendry, ; Pollock, Carr, Kreitals, & Phillips, ; Haxton & Cano, ; Jager et al, ). Dams are often constructed at or near lake sturgeon spawning areas, and as a result, many populations spawn immediately downstream of dams where operations can affect habitat quality and quantity (Randall, ; Dumont et al, ; Haxton et al, ; Kerr, Davison, & Funnell, ; Smith, Smokorowski, & Power, ). It is generally assumed that lake sturgeon hatch and recruitment success (defined herein as individuals surviving to age‐1) is improved downstream of dams if flow fluctuations are minimized during the spawning, egg incubation, and larval drift periods (Auer, ; Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Dams are often constructed at or near lake sturgeon spawning areas, and as a result, many populations spawn immediately downstream of dams where operations can affect habitat quality and quantity (Randall, ; Dumont et al, ; Haxton et al, ; Kerr, Davison, & Funnell, ; Smith, Smokorowski, & Power, ). It is generally assumed that lake sturgeon hatch and recruitment success (defined herein as individuals surviving to age‐1) is improved downstream of dams if flow fluctuations are minimized during the spawning, egg incubation, and larval drift periods (Auer, ; Smith et al, ). Using data from 23 rivers in Ontario, Haxton et al () found that recruitment failure was more evident in regulated systems, particularly peaking systems.…”
Section: Introductionmentioning
confidence: 99%